Shrinkage of ZrO2 green bodies manufactured by vat photopolymerization 3D printing - Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Lysenko E. N. Elena Nikolaevna; Vasiljev I. P. Ivan Petrovich; Svirkov Aleksandr Sergeevich A. S.; Tkachev D. A.; Verkhoshansky Ya. (2024, 2024)
Title screen